2012
DOI: 10.1021/jp303385x
|View full text |Cite
|
Sign up to set email alerts
|

pH-Replica Exchange Molecular Dynamics in Proteins Using a Discrete Protonation Method

Abstract: Protonation equilibria in biological molecules modulates structure, dynamics and function. A pH-Replica Exchange Molecular Dynamics (pH-REMD) method is described here to improve the coupling between conformational and protonation sampling. Under a Hamiltonian replica exchange setup, conformations are swapped between two neighboring replicas, which themselves are at different pHs. The method has been validated on a series of biological systems. We applied pH-REMD to a series of model compounds, to an terminally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…This scenario, although contrived, is a strong argument in favor of using a wide range of pH values (an extent of at least four units seems reasonable) or even using an expanded ensemble in which the pH is able to vary. 11,22,58 A complementary and/or alternative adjustment consists in selectively deactivating the inherent p K a algorithm for a small subset of residues that are either suspected of being important or have otherwise uncharacterized behavior. This can be done by trivially setting the inherent p K a equal to the pH.…”
Section: Resultsmentioning
confidence: 99%
“…This scenario, although contrived, is a strong argument in favor of using a wide range of pH values (an extent of at least four units seems reasonable) or even using an expanded ensemble in which the pH is able to vary. 11,22,58 A complementary and/or alternative adjustment consists in selectively deactivating the inherent p K a algorithm for a small subset of residues that are either suspected of being important or have otherwise uncharacterized behavior. This can be done by trivially setting the inherent p K a equal to the pH.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the data of 11 residues from the engineered mutants as well as the wild-type variant of SNase, McCammon and coworkers concluded that while the accuracy of the DpHMD method for predicting the p K a ’s of surface sidechains is high (root-mean-square error of 1.2 units), challenge remains for interior and coupled sites which require increased sampling and accelerated convergence [37]. To address this issue, the Roitberg group and others applied the pH-REX protocol to revisit the p K a calculation of hen egg white lysozyme (HEWL) [19] and small peptides [38, 39]. For more detailed discussion of the blind prediction results we direct the reader to the review article by Alexov et al [36].…”
Section: Recent Applications Of Constant Ph Molecular Dynamicsmentioning
confidence: 99%
“…The structure of the E2 monomer has not been reported previously; thus, the isolated E2 was adapted from the FI state with some equilibration through molecular dynamics to serve as a reference accounting for the possible metastable postdissociation state. The pH replica exchange MD (molecular dynamics) simulations were carried out to determine the pK a values of Asp, Glu, and His residues (54)(55)(56)(57). During the pH replica exchange MD simulations, the alchemical variable-λ is propagated according to the extended Hamiltonian equations of motions (54,55), characterizing varying protonation from fully deprotonated (λ = 1) to protonated (λ = 0) residues.…”
Section: Theory and Methodsmentioning
confidence: 99%